Studies on factors influencing conception rate in rural cattle - BHAGAT, R L; GOKHALE, S B (The Indian Journal of Animal Sciences, 2016)
The data of 14,937 farmers spread over 29 tehsils in 15 districts of six Indian states revealed mean conception rate as 55.96±0.31 %. State wise conception rate recorded in Bihar was 51.08±0.73%; Jharkhand; 62.03±0.63%; Maharashtra, 56.64±0.74%; Odisha, 59.24±0.91%; Punjab, 47.11±1.03%; Uttar Pradesh, 54.70±0.77% respectively, which was highly significant between the states. The education level of center in-charge, economic status of farmers, animal breed, animal parity, AI sequence and sire breed had significant effect on conception rate while effect of AI season did not significantly affect conception rate in rural animals across the states studied. It was recommended that due consideration need be given to consider effect of significant factors affecting conception rates while planning for improving conception rate in rural animals.